Mapping the common law concept of misrepresentation in contract under the Islamic Law - Norhoneydayatie Abdul Manap; Nik Abdul Rahim Nik Abdul Ghani; Amirah Madihah Adnan (Pusat Penyelidikan Syariah, Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2021)
Misrepresentation is the act of making a fraudulent misrepresentation by a party or parties to a contract to influence the other party to enter into a contract. This concept, which originated from common law, is applied in almost all Commonwealth countries, including Malaysia. The legal provisions in place to prevent misrepresentation in a contract are based on contract law theory. However, this misrepresentation concept has not been explicitly discussed from the Islamic Law perspective. Therefore, this study aims to identify the common law concept of misrepresentation in the contract law theory from the Islamic law perspective. The methodology used in this study is library research of the qualitative method. The study found that although the concept of misrepresentation is not visibly discussed in Islamic Law, however, the subjects of taghrīr would be considered to be the closest to misrepresentation.